INTERPRETIVE PREFERENCES BY SHEIKH MUHAMMAD TAHA AL-BALISANI FROM THE BEGINNING OF SURAT AL-JIN TO THE END OF SURAT AL-QIYAMAH. DATA COLLECTION AND STUDY - Mustafa Ayad Shehab Al-Douri; Imad Abbas Khalaf Al-Fahdawi (Journal Park Publishing, 2022)
All praise is due to Allah, and prayers and peace be upon His Messenger, Muhammad, his family and companions. The current study presented aimed at presenting the preferences of the scholar Al-Balisani and studying them comparatively in order to reach the most appropriate sayings. The study aimed to show the extent of the contribution of Iraqi scholars to the Islamic culture and serving the true Islamic religion. Here, we want to point out the concept of interpretation of Sheikh Al-Balisani to clarify what he confuses people from every outsider. We also want to point out that the ancients, with what they left us with a great inheritance, gained some of the suspicions, fillers and intruders from the narrations by the Israelites and the fake stories, in order to confront it from the contemporaries. So that, the interpretation comes out in its new form, without prejudice or deleting the old from the predecessor, because the old is a flowing source from which the innovators were inspired.